Modular Multilevel DC-DC Boost Converter for High Voltage Gain Achievement with Reduction of Current and Voltage Stresses - Samat, M. N. A.; Ponniran, A.; Kasiran, M. A. N.; Yatim, M. H.; Noor, M. K. R.; Jumadril, J. N. (International Journal of Integrated Engineering, 2020)
This paper presents a modular multilevel DC-DC boost converter for high voltage gain achievement with reduction of current and voltage stresses. Normally, conventional DC-DC boost converter (CDBC) has low voltage gain capability, higher current and voltage stresses which lead to high conduction loss of the semiconductor devices due to the circuit structure limitation. Therefore, 4-level synchronous modular multilevel DC-DC converter (SMMC) with Marx topology adaptation is considered to improve the limitation circuit structure of CDBC. Besides, the 4-level SMMC have high voltage gain achievement, it also has lower current and voltage stresses features. A 145 W and 48 V input voltage of 4-level SMMC has been designed and experimentally verified where the result is compared with CDBC. The results show that the CDBC required 0.76 of duty cycle while 4-level SMMC only require 0.5 duty cycle to achieve 200 V output voltage, respectively. Additionally, the current stress decreases by 75% on input inductor and 50% reduction from voltage stress of switching as compared to the CDBC. Consequently, the selection rating for the components can be decreased and higher efficiency can be obtained for the 4-level SMMC as compared to the CDBC.